Synthesis of Nano Chitosan as Carrier Material of Cinnamon’s Active Component - Ngadiwiyana Ngadiwiyana; Enny Fachriyah; Purbowatiningrum Ria Sarjono; Nor Basid Adiwibawa Prasetya; Ismiyarto Ismiyarto; Agus Subagio (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Development and innovation to improve the efficacy of active ingredients of a plant can be done by using nanoparticle encapsulation of chitosan, which has dual function of protecting natural extracts degradation and delivering natural extracts to the target site. Chitosan is a natural polymer that is nontoxic, mucoadhesive, biodegradable, and biocompatible. This polymer also has a low level of immunogenicity and can be prepared into nanoparticles in mild conditions that make it suitable for natural extracts delivery systems. This paper reported synthesis of chitosan nanoparticles for cinnamon’s natural extract delivery. Chitosan synthesis was carried out by chitin deacetylation isolated from shrimp shells. Chitosan characterization was done by measuring deacetylation degree by FTIR. Chitosan nanoparticles were prepared by ionic gelation method using tripolyphosphate as crosslinker. Morphology and particle size of nano chitosan were characterized using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). The result found that the yield of deproteinated chitin was 62.60%. Further process of demineralization resulted a yield of 52.60%, then depigmentation with a yield of 75.56%, and deacetylation with a yield of 79.02%. FTIR analysis showed that deacetylation degree of chitin into chitosan was found of 87.78%. Characterization by SEM found that nano chitosan has a particle size of 87 nm. While TEM images showed that the nano chitosan has a uniform shape and a lower physical aggregation.